PENGEMBANGAN E-BOOK EDUKASI PUBERTAS DAN ETIKA KEBERSIHAN BAGI SISWA SEKOLAH DASAR - Aliyah Salsabila; Citra Rosalyn Anwar; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to develop an e-book entitled "Ini Tubuhku, Ini Tanggung Jawabku" as an educational medium for puberty and personal hygiene ethics for fifth-grade elementary school students and to determine its validity and feasibility. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research was conducted at UPT SPF SD Inpres Perumnas Antang II, Makassar. The research subjects involved one material expert, one media expert, one learning expert, and 18 fifth-grade students as product users. Data were collected through questionnaires, interviews, and documentation, and were analyzed using descriptive quantitative and qualitative techniques. The results showed that the developed e-book obtained a validity score of 100% from the material expert, 92% from the media expert, and 95% from the learning expert, all of which were categorized as very valid. The limited trial conducted with students yielded a feasibility score of 92%, categorized as very feasible. These findings indicate that the developed e-book is suitable for use as an educational medium for puberty and personal hygiene ethics for elementary school students.